Hydroponic Website and App to Help Communities in the Pandemic Time - Davy Ronald Hermanus; Jajat Sudrajat; Titi Rahardjanti (Bina Nusantara University, 2021)
Hydroponic marketing app, is one of the solutions to accelerate employment problems for the community. Management of marketing information systems requires advanced technology, because information is one of the things that is very important for a company or institution time by time. Using a website media and its derivative media, namely social media app, that are well managed, delivered by thoughts and concepts of the lecturers from a university can help a community by social working. The problems of Neighbourhood Association (RT07) and Citizens Association (RW02) community members in Sarijadi Urban Village in Bandung can be overcome by increasing the interest of members of Empowerment and Family Welfare (PKK) and supported by Youth Organization (Karang Taruna) to cultivate Hydroponic plants.